Women in the Bible, Qumran and Early Rabbinic Literature Their Status and Roles - Heger, Paul (Studies on the Texts of the Desert of Judah, 2014)
Women in the Bible, Qumran and Early Rabbinic Literature: Their Status and Roles explores the different attitudes toward the woman's guilt for the expulsion from the Garden and human's calamities and the legal ramifications of her lower social and legal status regarding independence, ownership and membership in the community. Readership: Scholars of Old Testament, Qumran and rabbinic literatures, and intellectuals interested in the examination of these writings and in their influence on the contemporary status of women in Western society.